Harga Jual Keripik Rohaya: Analisis Biaya Produksi dan Distribusi - Raden Arum Setio Adi Ningrat; Nedi Hendri; Gustin Padwa Sari (Universitas Muhammadiyah Metro, 2026)
This study aims to determine the cost of chip production and to analyze the calculation of production costs and distribution costs in determining the selling price of chip products using the cost of product method. The research method used is a quantitative approach. The instrument in this study uses data from the Rohaya mother's chip factory and the results of interviews that have been conducted with factory owners and factory workers. The results of the study show that the calculation of the cost of production carried out by MSMEs at the Ibu Rohaya Chip Factory still uses a simple method. This study uses the cost of product method to make the cost of production information more accurate. Based on the comparison of the calculation of the cost of production and distribution costs using the company method and the cost of product method, the value of the cost of production produced has a considerable difference. This happens because business owners do not know how to calculate the cost of production properly and correctly, that is, they do not include costs correctly in the calculation of the cost of production.